1994
DOI: 10.1523/jneurosci.14-05-02708.1994
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence of trigeminal neuropathic pain following chronic constriction injury to the rat's infraorbital nerve

Abstract: Video recordings of free behavior and responses to mechanical facial stimulation were analyzed to assess whether chronic constriction injury (CCI) to the rat's infraorbital nerve (IoN) results in behavioral alterations indicative of neuropathic pain. A unilateral CCI was produced by placing loose chromic gut ligatures around the IoN. After CCI to the IoN, rats exhibited changes in both non-evoked and evoked behavior. Behavioral changes developed in two phases. Early after CCI (postoperative days 1–15), rats sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
515
2
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(561 citation statements)
references
References 85 publications
41
515
2
3
Order By: Relevance
“…The marked decrease of nociceptive threshold occurring 6 h after surgery in both IoN-CCI and sham rats probably corresponded to a traumatic response, because this allodynia-like behavior gradually disappeared in sham rats, as reported previously by others (Idanpaan-Heikkila and Guilbaud, 1999). The relative hyposensitivity of IoN-CCI rats observed at postoperative days 1 and 7 before the dramatic increase of responsiveness to mechanical stimulation is in line with previous data published on this model (Vos et al, 1994).…”
Section: Establishment Of Allodynia-like Behavior After Ion-cci or Snsupporting
confidence: 91%
See 3 more Smart Citations
“…The marked decrease of nociceptive threshold occurring 6 h after surgery in both IoN-CCI and sham rats probably corresponded to a traumatic response, because this allodynia-like behavior gradually disappeared in sham rats, as reported previously by others (Idanpaan-Heikkila and Guilbaud, 1999). The relative hyposensitivity of IoN-CCI rats observed at postoperative days 1 and 7 before the dramatic increase of responsiveness to mechanical stimulation is in line with previous data published on this model (Vos et al, 1994).…”
Section: Establishment Of Allodynia-like Behavior After Ion-cci or Snsupporting
confidence: 91%
“…Unilateral chronic constriction injury to the infraorbital nerve was performed under direct visual control using a Zeiss microscope (10 -25ϫ) essentially as described by Vos et al (1994). Briefly, the head was fixed in a HorsleyClarke stereotaxic frame, and a midline scalp incision was made, exposing skull and nasal bone.…”
Section: Chronic Constriction Injury To the Infraorbital Nervementioning
confidence: 99%
See 2 more Smart Citations
“…57 We reported that HSV-mediated expression of proenkephalin reduces pain-related behavior in a rodent model of pain caused by cancer in bone. 58 In a rat model of trigeminal neuropathic pain which shares numerous similarities with human trigeminal neuralgia and trigeminal neuropathic pain, 59 Pohl and coworkers demonstrated that transgene-derived met-enkephalin significantly reduced mechanical hyperresponsiveness. 60 This antiallodynic effect was reversed by both the opioid receptor antagonist naloxone and the peripherally acting antagonist naloxone methiodide.…”
Section: Herpes Simplex Virus Vectormentioning
confidence: 99%